2017
DOI: 10.1007/s10554-017-1128-9
|View full text |Cite
|
Sign up to set email alerts
|

Agreement of tricuspid annular systolic excursion measurement between transthoracic and transesophageal echocardiography in the perioperative setting

Abstract: Our study showed that the right ventricular function can be accurately and precisely estimated using TAPSE measurement by TEE in the midesophageal four chamber and deep transgastric right ventricle view at 0° using anatomical M-mode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…In contrast, the M-mode in the transgastric view although showing high feasibility and reproducibility carries a systematic underestimation of TAPSE compared with TTE. 13,30 Still, the sequential changes in M-mode TAPSE seen in the current study was in agreement with the anatomic M-mode in the transgastric view, which as described has shown high feasibility, high reproducibility, as well as high interchangeability with TTE TAPSE, thus strengthening the findings.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In contrast, the M-mode in the transgastric view although showing high feasibility and reproducibility carries a systematic underestimation of TAPSE compared with TTE. 13,30 Still, the sequential changes in M-mode TAPSE seen in the current study was in agreement with the anatomic M-mode in the transgastric view, which as described has shown high feasibility, high reproducibility, as well as high interchangeability with TTE TAPSE, thus strengthening the findings.…”
Section: Discussionsupporting
confidence: 89%
“…13 In that study we found that anatomic M-mode in the transgastric view showed the best performance compared with TTE throughout surgery. Flo Forner and colleagues 30 have also shown good agreement between TTE and TEE anatomic M-mode TAPSE, but only in the preoperative setting-not throughout surgery. In contrast, the M-mode in the transgastric view although showing high feasibility and reproducibility carries a systematic underestimation of TAPSE compared with TTE.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Alternative views with superior alignment exist for visualization of the RV [22]. Particularly, the modified deep transgastric view focusing the right ventricle and the transgastric RV inflow view has been evaluated in the literature, however, showing underestimation of TAPSE by TEE using these alternative views in comparison to TAPSE by TTE using an apical four-chamber view [26,27]. Therefore, alternative and less angle-dependent techniques seem more promising.…”
Section: Conventional Echocardiographic Parametersmentioning
confidence: 99%
“…Therefore, alternative and less angle-dependent techniques seem more promising. Measurement of TAPSE by anatomic M-mode which evaluates two-dimensional pixel samples along a freely positioned cursor line presented increased precision [26,28]. A further approach is to measure TAPSE with speckle-tracking echocardiography, which is mainly angle-independent [28,29].…”
Section: Conventional Echocardiographic Parametersmentioning
confidence: 99%